Principles of Pharmacotherapy of Seizures and Status Epilepticus - Der-Nigoghossian, Caroline; Tesoro, Eljim P.; Strein, Micheal; Brophy, Gretchen M. (Seminars in Neurology, 2020)
Status epilepticus is a neurological emergency with an outcome that is highly associated with the initial pharmacotherapy management that must be administered in a timely fashion. Beyond first-line therapy of status epilepticus, treatment is not guided by robust evidence. Optimal pharmacotherapy selection for individual patients is essential in the management of seizures and status epilepticus with careful evaluation of pharmacokinetic and pharmacodynamic factors. With the addition of newer antiseizure agents to the market, understanding their role in the management of status epilepticus is critical. Etiology-guided therapy should be considered in certain patients with drug-induced seizures, alcohol withdrawal, or autoimmune encephalitis. Some patient populations warrant special consideration, such as pediatric, pregnant, elderly, and the critically ill. Seizure prophylaxis is indicated in select patients with acute neurological injury and should be limited to the acute postinjury period.
Keywords: status epilepticus; seizure; treatment; antiseizure drugs